(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Pulmonary tuberculosis (TB) remains a public health problem in Indonesia with an estimated 1,082,000 cases in 2023. At the Sei Mencirim Community Health Center, the success of pulmonary TB treatment still faces challenges due to patients who do not complete therapy. This study aims to analyze the influence of individual characteristics, knowledge, family support, and support from health workers on the success of pulmonary TB treatment in 2025. The study used a cross-sectional design with a quantitative approach. The study population was 181 pulmonary TB patients who had undergone Anti-Tuberculosis Drug (OAT) therapy for 6 months, with a sample of 64 respondents selected through simple random sampling. Data were collected using questionnaires and medical records, then analyzed using the Chi-Square test and logistic regression. The results showed that age, education, gender, knowledge, family support, and support from health workers were significantly associated with the success of pulmonary TB treatment (p<0.05). Descriptively, 29.7% of respondents were declared cured, 37.5% completed the full treatment, and 32.8% were unsuccessful. Family and healthcare provider support plays a crucial role in improving patient adherence during treatment. Therefore, strengthening education and social support is necessary to improve the success of pulmonary TB treatment.